(untitled) (Advancements in Homeopathic Research, 2022)
Background: Subclinical hypothyroidism is a common problem with prevalence of 3% to 8% in population without known thyroid disease. Prevalence increases with age and is higher in women. Subclinical hypothyroidism may progress to overt hypothyroidism. Objective:To assess the usefulness of homoeopathic medicines on inhibition of serum TSH in patients of hypothyroidism, a clinical study was conducted at Gaurang Clinic and Centre for Homoeopathic Research, Lucknow, India. Methods: A total of 347 patients have been screened with TSH above 6.0 mIU/L, out of which 202 were found fit for the study. The medicines have been selected on the basis of principles of homoeopathy. Serum TSH was assessed before and after treatment. Results: After comparing pre and post treatment results, the difference in mean values of TSH were 31.91 ± 3.97 vs. 16.69 ± 2.48, improvement=15.23 ± 2.68, t=5.68, p<0.001, which was found statistically significant. Calcarea carb (n=57) Lycopodium (n=43), Pulsatilla (n=43) and Natrum mur (n=39) were found to be most useful medicines. Conclusion: Results obtained from the study are encouraging with findings that homoeopathic medicines were able to inhibit serum TSH level significantly in 176 (87.1%.) patients. However, randomized control trials are needed for further validation of role of homoeopathic medicines in cases of hypothyroidism.